Multilinear trajectories: Polanyi, The Great Transformation and the American exception - Lacher, Hannes (Karl Polanyi and twenty-first-century capitalism, 2020)
Karl Polanyi’s call, in The Great Transformation, for a re-embedding of markets, is widely understood to have come to fruition in the American New Deal and in the post-war order of ‘embedded liberalism’. Based on archival sources, this chapter shows that Polanyi’s political project was far more radical. Polanyi initially considered the New Deal a vital response to the problems of American capitalism, but one that would have little relevance to the problems and dynamics of European societies. There, he considered a socialist transformation both possible and necessary. But eventually, Polanyi realised that the US, far from remaining an exceptional outlier of ‘nineteenth-century civilisation’, was imposing its model on Britain and Europe. The internationalisation of the American New Deal in the Bretton Woods order marked the defeat of Polanyi’s political project.